Resecentrum i perifera lägen : Ett konceptförslag för resecentrum i Piteå kopplat till Norrbotniabanan - Standar, Matilda (Luleå tekniska universitet, Institutionen för samhällsbyggnad och naturresurser, 2019)
At present, a large part of the products from the north is transported on the main line through upper Norrland, which handles all railway transports through Norrland. The track does not meet today´s requirements for freight transport because of its curvy and hilly traction, its only track and the fact that it is located far from the coast where most industries are situated. In 2002, the investigation of a new coastal railway began, which can relieve the main line from freight traffic, but also promote passenger transport by dimidiated travel times and increased communication between the cities. The new railway was named Norrbotniabanan and is planned to pass through the larger cities along the coast. Piteå is the city that has the most possible route options and potential locations for the railway station. After a number of investigations, only two alternative tractions through Piteå remains, alternatives P1 and P2. In alternative P1, or the Coastal route, Norrbotniabanan is supposed to run parallel with E4. A travel center is planned to be located south of Lomtjärn and west of E4. In the other alternative P2, or the Central route, the track would pass through the center of Piteå where the travel center would be located also. The purpose of this work has been to investigate the potential of Lomtjärn Travel Center in the alternative coastal route of the Norrbotniabanan railway. The aim was to be able to specify which features that should be implemented to achieve the best design for the Lomtjärn Travel Center in its peripheral position, with regard to social and ecological sustainability, to promote passenger transport. In order to achieve the aim information was obtained by a literature study linked to the railway station's basic properties and importance to the city. Furthermore, a study was conducted of existing peripheral stations to gather inspiration and see how others had solved various functions connected to the station. A site analysis was also conducted where the travel centers location previously ...